Pendapat dan Daya Beli Petani Karet terhadap Kebutuhan Pokok Saat Pandemi COVID-19 di Desa Gunung Riut Kabupaten Balangan - Ghazali, Ahmad; Wardhana, Ali (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to determine rubber farmers' income and purchasing power for basic needs during the COVID-19 pandemic in Gunung Riut Village, Balangan Regency. This research is a type of descriptive research with a quantitative approach, which was carried out in January-March 2022. The research method used is analyzing rubber farmers' purchasing power against basic needs with the formula andthen analyzing income with the formulawith the number of respondents, as many as 65 rubber farmers in Gunung Riut Village, Balangan Regency. The results of this study prove that the total income of rubber farmers during the COVID-19 pandemic is Rp. 116.570.000 with an average income of Rp. 1.793.384. The purchasing power of rubber farmers for basic needs during the COVID-19 pandemic has not decreased too much because the income of each rubber depends on the price of rubber offered by collectors, unless the rubber factory is difficult to move due to the COVID-19 pandemic, that is what will make the income of rubber farmers decrease